CHEMICAL CHARACTERIZATION OF PM2.5 DERIVED FROM AGRICULTURAL BIOMASS BURNING ON PADDY, MAIZE AND SUGARCANE COMMODITIES - Fauziah Lu'ayi, Aulia
Indonesia is an agrarian country that is a majority of the population consuming rice and corn as a staple food, as well as using sugar cane as the main basic ingredient for daily use of sugar. However, farmers tend to do open burning to their agricultural biomass. This proved to be an easy, inexpensive and trustworthy move that can handle the accumulation of the remaining agricultural biomass rapidly, and can also be a way of controlling the wild grass and able to restore nutrients to the soil with a short period of time. The agricultural biomass open burning practice is emitted PM2.5 which causes air pollution. The research of air pollution modelling in Indonesia often uses the default input source profile from global database. This gives less representative output of modesl that are off the local situation in Indonesia. Therefore, it is necessary to develop a local source profile of PM2.5 from the emissions of agricultural biomass burning in Indonesia. The latest research done by Hafidawati (2019) has reported local emission factors of PM2.5 and black carbon (BC) from agricultural biomass burning in West Java. However, other parameters such as element and ion of PM2.5 derived from agricultural biomass burning have not been investigated in the study. In addition, the local source profile of agricultural biomass burning for element and ion content is not yet present in Indonesia. In response to this problem, the aim of this research is to develop local source profile through chemical characterization in the form of element and ion of PM2.5 derived from agricultural biomass burning on rice, corn, and sugarcane commodities. This research continues the research of Hafidawati (2019), by conducting chemical characterization from her samples of research. Sampling had performed after harvesting time in the field according to local farmer’s habits. Sampling had carried out burning at smoldering phase using a Minivol sampler with flowrate 5lpm. The filter used in the form of PTFE, which is hydrophobic, diameter 47 mm, with a pore size of 0.45 ?m. The sample filter analyzed in the laboratory. Elemental content analysis using energy dispersive x-ray fluorescence (ED-XRF) and ion analysis using ion chromahography (IC). Chemical characteristics of elements of PM2.5 potently developed into a local source profile and could become one of the important inputs in the local receptor model then. Local source profile of the research as an input expected to produce more representative output model of agricultural biomass burning case in Indonesia. Therefore, a more responsive recommendation of policy on agricultural biomass burning in Indonesia can be performed. The results showed the dominant elements (concentration and contribution) of PM2.5 from agricultural biomass burning emission of paddy, sugar cane, and maize commodities namely: Pb, Mg, Na, Zn, and Al. Ions dominant PM2.5 from agricultural biomass burning emissions in the field for paddy, sugar cane, and maize commodities respectively K+, Mg2+, Cl-, NH4+, SO42- ; Ca2+, Mg2+, Cl-, SO42-, K+; and Cl-, NH4+, Ca2+, Na+, K+. The composition of chemical parameters indicates that black carbon, 21 elements, along with 8 ions became PM2.5 constituents of paddy biomass burning emissions (5.93 % - 11.29 %), sugar cane (5.79 % – 11.43 %), and maize (3.77 % – 8.19 %). For confidence level 95%, the average significant concentration and/or contribution of chemical parameters came from emission of maize biomass burning.